Evaluasi Bangunan Gedung Kampus I Universitas Bosowa Dengan Metode Pendekatan Desain Berbasis Kinerja - Arif, Muh Panca Zainuddin; Abduh, M. Natsir; Setiawan, Arman (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
This study was conducted to determine the collapse pattern described as a capacity curve so that the performance level of the structure can be known based on FEMA 356. As well as the formation of plastic joints on the column beams, the study used spectrum response with the ETABSv19 program.  Basedon the direction of the XZ and YZ methods The capacity curve and FEMA 356 produces Damage Control (DC), where thebuilding condition occurs during an earthquake.   This study shows the displacement value based on pushover analysis, SNI 1726-2019, and direct measurement. Where seen in direct measurements and displacement targets, getting almost the same value of 11 cm to 15 cm. With provisions based on SNI 1726-2019, which is 31 cm, the maximum limit of pushover analysis results for the X direction is 72 cm and the Y direction is 40 cm. It can be concluded that if the provisions based on SNI 1726-2019 > direct measurement and displacement target, the building structure is still in a Safe State